Quantification of Helicobacter pylori and its oncoproteins in the oral cavity: A cross‐sectional study. (6th February 2022) - Sekar, Ramya; Murali, Preethi; Junaid, Mohammed
Abstract: Objective: To identify Helicobacter pylori (H. pylori) and related oncogenic and virulent proteins (CagA and VacA) in patients with gingivitis, periodontitis, oral cancer and gastric cancer. Methods: Subgingival plaque samples were collected from 90 individuals with either gingivitis/periodontitis (group A, n = 30), oral cancer (group B, n = 30) and gastric cancer (group C, n = 30). H. pylori was identified by real‐time polymerase chain reaction (RT‐PCR). The virulent organisms were detected by identification of proteins CagA and VacA through Enzyme Linked Immuno‐Sorbent Assay (ELISA). Results: We identified the presence of H. pylori in subgingival plaque samples among a large majority (76/90) of our study cohort. The proportions of CagA and VacA identified among H. pylori individuals with periodontal inflammation and oral cancer were lower than those diagnosed with gastric cancer. Furthermore, the relative risk of oral cancer based on the presence of the organism was no different to those with gingivitis/periodontitis. Conclusion: The findings of our study do not indicate significant association between the organism and oral cancer, but preludes that the oral cavity could act as a potential niche for H. pylori . The possibility for CagA and VacA proteins to be pathogenic in oral cavity is highly possible and must be researched extensively.